EMERGING TECHNOLOGIES IN BOKO HARAM'S OPERATIONS AND COUNTER-TERRORISM EFFORTS IN CENTRAL AFRICA - Minko, Abraham Ename (Journal of Terrorism Studies, 2025)
The interplay between terrorism and technology in Central Africa has intensified, particularly with Boko Haram’s rise. This research explores how emerging technologies enhance Boko Haram's operations and the corresponding counter-terrorism efforts. It examines Boko Haram’s use of social media for recruitment, encrypted messaging for secure communication, and advanced weaponry like drones and improvised explosive devices (IEDs). These technologies have expanded Boko Haram’s reach and operational efficiency, challenging security forces. The study also evaluates technological countermeasures implemented by Central African governments and international bodies, including surveillance, cyber intelligence, and data analytics. It assesses the effectiveness of these measures, noting successes and obstacles such as limited resources and rapidly evolving threats. Using a qualitative method, the research explores cybersecurity dynamics, including Boko Haram’s cyber-attacks on critical infrastructure and its use of the internet for radicalization. The study identifies gaps in current cybersecurity defenses and provides strategic recommendations for improvement. These include adopting advanced surveillance and data analysis tools, enhancing regional cooperation for intelligence sharing, and increasing investment in cybersecurity. The aim is to develop a more effective counter-terrorism strategy informed by technological advancements.